DETERMINASI PROFITABILITAS PERUSAHAAN SEKURITAS GO PUBLIC - Nuryani, Anum; Jati, Waluyo (JURNAL LENTERA AKUNTANSI, 2023)
The purpose of this study is to examine and analyze the factors that affect profitability in securities companies that list their shares on the IDX. The method used begins with a search for secondary data from the period's financial statements. From 6 existing companies, 5 company samples were selected with a research period of 2016-2021. The data obtained is then obtained with the help of eviews to obtain the appropriate estimation model. Research is designed starting from problem identification, literatal studies, data search and processing, data presentation, distribution and withdrawal. The results of the study found that the factors that affect profitability, namely cash coverage against debt, debt to equity ratio and asset turnover have a significant effect on profitability supported by a coefficient of determination of 96%. Keywords: Profitability, Securitas, CKH, DER, TATO, ROA